(Re)construction of the identity of highly educated returnees: The case of Serbia - Vesković Anđelković, Milica; Vasojević, Nena A. (Sociološki pregled, 2024)
The aim of this paper is to analyze empirical data collected through focus-group research that examined the experience and formation of the identity of highly educated returnees after a period of studying abroad. We start from the theoretical assumption of identity as a social category, which means that it is the result of the interaction between people, institutions and practice, and thus it is changeable, in the constant process of formation and never completed. The emphasis will be placed on the analysis of building the respondents’ identity and their attitudes towards individual identity components. From interviews it can be concluded that migration experience has largely affected the building and understanding of own identity, that it remains open to influences of new social environments, while also preserving the contours of national culture.